'Domain structures – heterophases – phase contents' relations in lead-free ferroelectric solid solutions. (26th April 2019) - Topolov, V. Yu.
Abstract: Examples of two- and three-phase structures in BaTiO3 -based ferroelectric solid solutions are first analyzed within the framework of the united model. The role of domain orientations and heterophases containing the tetragonal phase are discussed in the context of the stress relief at interfaces that separate the ferroelectric phases and two-phase regions. Relations between the domain (twin) structures and phase contents are studied for three-phase states in (1 −  x )BaTiO3  −  x CaHfO3, (1 −  x )BaTiO3  −  x CaSnO3, and (1 −  x  −  y )BaTiO3  −  x CaTiO3  −  y BaZrO3 with compositions near the morphotropic phase boundary. In these materials, volume fractions of the tetragonal, orthorhombic and rhombohedral phases are interpreted in terms of the united model by taking into account analogies between domain orientations in the adjacent phases and minimum numbers of domain types (mechanical twins) therein. Calculated results on the phase content are consistent with experimental room-temperature data on the three aforementioned solid solutions.